Minigene‐based splicing analysis and ACMG/AMP‐based tentative classification of 56 ATM variants. Issue 1 (15th July 2022) - Bueno‐Martínez, Elena; Sanoguera‐Miralles, Lara; Valenzuela‐Palomo, Alberto; Esteban‐Sánchez, Ada; Lorca, Víctor; Llinares‐Burguet, Inés; Allen, Jamie; García‐Álvarez, Alicia; Pérez‐Segura, Pedro; Durán, Mercedes; Easton, Douglas F; Devilee, Peter; et al.
Abstract: The ataxia telangiectasia‐mutated (ATM) protein is a major coordinator of the DNA damage response pathway. ATM loss‐of‐function variants are associated with 2‐fold increased breast cancer risk. We aimed at identifying and classifying spliceogenic ATM variants detected in subjects of the large‐scale sequencing project BRIDGES. A total of 381 variants at the intron–exon boundaries were identified, 128 of which were predicted to be spliceogenic. After further filtering, we ended up selecting 56 variants for splicing analysis. Four functional minigenes (mgATM) spanning exons 4–9, 11–17, 25–29, and 49–52 were constructed in the splicing plasmid pSAD. Selected variants were genetically engineered into the four constructs and assayed in MCF‐7/HeLa cells. Forty‐eight variants (85.7%) impaired splicing, 32 of which did not show any trace of the full‐length (FL) transcript. A total of 43 transcripts were identified where the most prevalent event was exon/multi‐exon skipping. Twenty‐seven transcripts were predicted to truncate the ATM protein. A tentative ACMG/AMP (American College of Medical Genetics and Genomics/Association for Molecular Pathology)‐based classification scheme that integrates mgATM data allowed us to classify 29 ATM variants as pathogenic/likely pathogenic and seven variants as likely benign. Interestingly, the likely pathogenic variant c.1898+2T>G generated 13% of the minigene FL‐transcript due to the use of a noncanonical GG‐5'‐splice‐site (0.014% of human donor sites). Circumstantial evidence in three ATM variants (leakiness uncovered by our mgATM analysis together with clinical data) provides some support for a dosage‐sensitive expression model in which variants producing ≥30% of FL‐transcripts would be predicted benign, while variants producing ≤13% of FL‐transcripts might be pathogenic. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.